Footnotes and references in Lev Loseff’s poetry - Павловец, Михаил (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
Poems which contain footnotes, including those with references, are paramount in the poetry by Lev Loseff. They add “philologism” to his poetry and determine the special ways which the poet uses to create the lyrical subject in his works. The lyrical subject in Loseff's poetry has two hypostases: the one of a poet and the one of a commentator. Lyrical discourse is organically combined with the philological one, and the subject’s selfreflection is combined with meta-reflection of the text.